Lnc-ing pluripotency maintenance and early differentiation in human pluripotent stem cells - Lu, Pei; Li, Mao; Zhang, Donghui; Jiang, Wei (The FASEB journal, 2021)
Pluripotency maintenance and lineage differentiation are two major characteristics of human embryonic and induced pluripotent stem cells. The determination of self-renewal or differentiation is under the exquisite control of the gene regulatory network, which is composed of transcription factors, signaling pathways, metabolic factors, chromatin or histone modifiers, miRNAs, and lncRNAs. Growing evidence has shown that long noncoding RNAs (lncRNAs) play important roles in epigenetic, transcriptional, and posttranscriptional gene regulation during the cell fate determination of pluripotent stem cells. Here, we summarize recent reports of lncRNA functions in pluripotency maintenance/exit and the early germ layer specification of human pluripotent stem cells. We also illustrate four major lncRNA functional mechanisms according to different types of cofactors: chromatin or histone modifiers, transcription factors, canonical and noncanonical RNA-binding proteins, and miRNAs. Further understanding of lncRNA-based regulation will provide more insights into the drivers manipulating cell fate and promote the therapeutic and research potential of human embryonic and induced pluripotent stem cells.